Design of school SPP bookkeeping data collection application - Syaira, Nesya; Lubis, Amanda Putri; Kristiyanto, Yogi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
School tuition fee (SPP) management is still widely conducted manually, which may lead to recording errors, reporting delays, and a lack of financial transparency. This study aims to design and implement a web-based SPP bookkeeping data collection system to improve the effectiveness and accuracy of school financial administration. The research method applied is the System Development Life Cycle (SDLC) using the Waterfall model, which includes requirement analysis, system design, implementation, and testing stages. The results indicate that the developed system is capable of managing student data, recording SPP payments, and generating structured payment reports and histories. The system simplifies data retrieval and accelerates financial reporting processes. Furthermore, the web-based system reduces recording errors commonly found in manual bookkeeping. The discussion reveals that the computerized system improves time efficiency and enhances transparency in school tuition payment management. In addition, the system is user-friendly and easy to operate for administrative staff. Therefore, the proposed web-based SPP bookkeeping system is expected to support professional, accountable, and sustainable school financial management.